Effectiveness of medium-chain triglyceride diet and low glycemic index therapy in drug-resistant childhood epilepsy: a systematic review, meta-analysis, and meta-regression - Wiradarma, Elbert; Khosama, Herlyani; Warouw, Finny; Wariki, Windy M. V.; Jehosua, Seilly Yunita; Pertiwi, Junita Maja (Faculty of Medicine, Universitas Trisakti, 2025)
Background Drug-resistant epilepsy (DRE) challenges clinical management, with many patients failing to find relief. Medium-chain triglyceride diet (MCTD) and low glycemic index therapy (LGIT) are emerging variants of the ketogenic diet. MCTD and LGIT show promise but lack clear efficacy data. The purpose of this systematic review was to evaluate and compare the efficacy of MCTD and LGIT in the management of pediatric patients with DRE. Methods Four databases were searched (PubMed, Embase, Scopus, and Cochrane Library) from November 2024 to February 2025. Two independent reviewers meticulously screened titles, abstracts, and full texts, ensuring adherence to predefined criteria. Data extraction encompassed study characteristics, participant demographics, intervention details, and outcomes, including seizure frequency, percentage reduction, and adverse events. Statistical analyses were performed using R 4.2.2 software, assessing heterogeneity with Cochrane Q and I² and utilizing random-effects and common-effects models. Results From 1489 articles found, 487 duplicates were removed, 897 were excluded based on title and abstract screening, and of the 47 full-text articles assessed for eligibility, 31 articles were excluded, resulting in 16 articles (9 MCTD and 7 LGIT) included in this review. The pooled estimates for the proportion of children achieving seizure freedom, ≥90% seizure reduction, and ≥50% seizure reduction following the intervention were comparable between the MCTD and LGIT groups. Based on the random-effects model, the overall success proportion of MCTD in reducing seizure frequency was 0.20 [95 % Confidence Interval (CI), 0.14-0.27] (p<0.01). Meanwhile, in the LGIT group, the overall success proportion was 0.27 [95% CI,0.14- 0.45] (p<0.01). Conclusion Both MCTD and LGIT demonstrate comparable efficacy, and no definitive conclusion can be drawn regarding the superiority of one diet over the other.